Karakter Morfologi Tanaman Kedelai (Glycine max (L.) Merril) Tercekam Kekeringan Melalui Aplikasi Antioksidan - Ahmad Sadam; Asil Barus; Mariati (Talenta Publisher, 2018)
Decreasing soybean production can not fulfill the needs of soybeans in Indonesia, one of the main causes is the decreasing of agricultural land. To increase soybean production in Indonesia can be reached by expanding the planting area, namely by utilizing the potential land. This research was conducted in the plastic house of Faculty of Agriculture, the University of Sumatera Utara, Medan with the height of place ± 25 meters above sea level from August 2016 until November 2016, using randomized block design with 2 factors of treatment. the first factor is drought stress with 3 levels ie KL 80%; KL 60%; TOS 40% and the second factor is the provision of antioxidants with 2 kinds of salicylic acid and ascorbic acid. The results showed that drought stress treatment significantly affected the number of empty pods per plant.